Face recognition using multiple recognizers - Vatsa, M.; Singh, R.; Gupta, P. (2004 IEEE International Conference on Systems, Man and Cybernetics, 2004)
In this paper we have presented a fusion of three face recognizers, LFA, LBA and KDDA, which combines the three confidence measure factors (CMFs) using a RBF neural network. This strategy is used to increase the accuracy of the face recognition system. The recognizer is tested on AT&T-ORL, AR and IITK face database and the results are found to be more than 95%.